Measuring hope: Standardization of the Czech version of the Adult Dispositional Hope Scale in healthy adults - Ociskova, Marie; Sobotkova, Irena; Prasko, Jan; Mihal, Vladimir (Neuro endocrinology letters, 2017)
OBJECTIVES: Hope is an important factor that influences mental state of individuals and efficacy of systematic and supportive psychotherapy. The goal of the study was to translate the Adult Dispositional Hope Scale (ADHS) to Czech, evaluate its psychometric properties and create norms to interpret the scale scores. METHODS: The scale consists of twelve items. Four items assess the ability of pathway thinking, four items measure agency, and the remaining four items are fillers that are not interpreted. There were 394 adult participants with negative psychiatric history who completed the ADHS and BDI-II. Their mean age was 27.1±11.7 years, most of them were women (n=303; 76.9%). RESULTS: There was no significant relationship between age or sex and hope. Reliability was analyzed by Cronbach alpha (α=0.82) and the split-half method (Spearman-Brown coefficient = 0.81). The factor structure of the scale was approved by the results of exploratory and confirmatory factor analysis, except the ninth item that similarly saturated both subscales. The ADHS moderately negatively correlated with BDI-II. Norms were created for the scores of the entire scale and both subscales. CONCLUSION: The Czech version of the Adult Dispositional Hope Scale shows adequate psychometric properties.
Keywords: Male; Factor Analysis, Statistical; lidé středního věku; Sex Factors; Age Factors; Humans; Reproducibility of Results; depresivní poruchy; Middle Aged; senioři; reprodukovatelnost výsledků; Česká republika; mužské pohlaví; Czech Republic; Female; mladiství; Aged; psychometrie; Psychometrics; ženské pohlaví; věkové faktory; mladý dospělý; Adult; Young Adult; sexuální faktory; Adolescent; dospělí; lidé; Depressive Disorder; faktorová analýza statistická